Prawnokarne instrumenty zapobiegania i zwalczania terroryzmu w polskim prawodawstwie - Śledź, Mieczysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article examines the instruments for preventing and combating terrorism in Polish criminal law. The Act of 16 April 2004 amending the Criminal Code and other acts of parliament introduced a definition of terrorist offence into the Polish Criminal Code. According to this definition, “A terrorist offence is a prohibited act punishable by a maximum custodial sentence of at least 5 years committed in order to: 1 seriously intimidate many persons, 2 compel a public authority of the Republic of Poland or of another state or an agency of an international organisation to perform or abstain from performing certain acts, 3 cause serious destabilisation in the political system or economy of the Republic of Poland, another state or international organisation. A threat to commit such an act should also be considered a terrorist offence.”
Keywords: prokuratura; prokuratura apelacyjna; przestępstwo terroryzmu; prawo karne; zagrożenia bezpieczeństwa